Evaluating the Shear Bond Strength of Repaired Composites Using Different Surface Treatments and Repair Materials: An In-Vitro Comparative Study - Prinaxy Byxyx; Ajay Kumar Nagpal; Prashasti Pandey; Darshan Das; Mihir Anand; Anupama Pradhan (Journal of Pharmacy and Bioallied Sciences)
Introduction: Composite resin is commonly used in dental restorations, though it is prone to degradation over time. Repairing these restorations is often preferable for issues such as discoloration, small areas of decay near the restoration margin, or for preserving tooth health without the need for complete removal. Method: Sixty acrylic blocks with cavities were restored using FILTEK-Z-250 XT composite resin, which was then light-cured. After 300 thermal cycles, the blocks were divided into three groups: control, diamond bur-abraded, and aluminum oxide air-abraded. Each group was further subdivided into two subgroups, treated with either Ivoclar Tetric N-bond or 3M ESPE Single Bond Universal adhesive. Shear bond strengths (SBSs) were tested after applying additional composite, and the types of fractures were analyzed. Results: The air-abrasion group (Group III) exhibited the highest SBS values compared to the other groups. Specifically, Group IIIb (air-abrasion combined with 3M ESPE Single Bond Universal adhesive) recorded the highest SBS values overall and within its subgroup. Conclusion: Treating the composite material’s surface with mechanical methods, especially air-abrasion, improves its repairability.